Efektivitas Penyaluran Zakat Produktif Melalui Program Pemberdayaan Ekonomi dalam Meningkatkan Kesejahteraan Mustahik - Septian Nugraha; Zaini Abdul Malik; Neng Dewi Himayasari (Jurnal Riset Ekonomi Syariah, 2024)
Abstract. One of the real problems faced by the Indonesian nation is the inequality of income distribution, poverty and the level of welfare of its people. Zakat is a concept offered by religion to alleviate or overcome poverty through existing programs, such as productive zakat, and empowerment. This study aims to find out how the economic empowerment program of Lazismu West Java in improving mustahik welfare to find out how the effectiveness of productive zakat distribution through the Lazismu West Java economic empowerment program in improving mustahik welfare This research uses quantitative methods with a descriptive approach. Data sources from primary data and secondary data, Data collection techniques with field research, documentation, literature studies and questionnaires. The analysis method uses quantitative descriptive analysis, validity test, reliability test, Normality test, simple linear regression test, and hypothesis test.The result of this study is the economic empowerment program in improving mustahik welfare with several fields, education, economy, social humanity and health, with several programs in it that support the sustainability of the program, the result of the analysis is the distribution of productive zakat through empowerment programs running effectively towards improving mustahik welfare. Abstrak. Salah satu permasalahan nyata yang dihadapi bangsa Indonesia adalah ketimpaan distribusi pendapatan, kemiskinan serta tingkat kesejahteraan masyarakatnya.Zakat merupakan sebuah konsep yang ditawarkan oleh agama untuk mengantaskan atau mengatasi kemiskinan melalui program program yang ada, seperti zakat produktif, dan pemberdayaan. Penelitian ini bertujuan untuk mengetahui bagaimana program pemberdayaan ekonomi Lazismu Jawa Barat dalam meningkatkan kesejahteraan mustahik dan untuk mengetahui bagaimana efektivitas penyaluran zakat produktif melalui program pemberdayaan ekonomi Lazismu Jawa Barat dalam meningkatkan kesejahteraan mustahik Penelitian ini menggunakan metode kuantitatif dengan pendekatan deskriptif. Sumber data dari data primer dan data sekunder, Teknik oengumpulan data dengan penelitian lapangan, dokumentasi, studi kepustakaan dan kuisioner. Adapun metode analisis menggunakan analisis deskriptif kuantitatif, uji validitas, uji reliabilitas, uji normalitas uji regresi linier sederhana, dan uji hipotesis.Hasil dari penelitian ini yaitu program pemberdayaan ekoonomi dalam meningkatkan kesejahteraan mustahik dengan beberapa bidang, pendidikan, ekonomi, sosial kemanusiaan dan kesehatan, dengan beberapa program didalamya yang mendukung keberlangsungan program tersebut , hasil analisis nya adalah penyaluran zakat produktif melalui program pemberdayaan berjalan efektif terhadap peningkatan kesejahteraan mustahik.